Ondansetron use is associated with increased risk of acute kidney injury in ICU patients following cardiac surgery: a retrospective cohort study - Xu, Feiyi; Gong, Xun; Chen, Wei; Dong, Xiaomin; Li, Jiang (Frontiers in Pharmacology, 2024)
BackgroundOndansetron is widely used for prophylaxis of postoperative nausea and vomiting (PONV) after general anesthesia. While previous studies have emphasized its early use, the effects of ondansetron in intensive care unit (ICU) patients following cardiac surgery remain unclear. This study investigates the association between postoperative ondansetron exposure and the risk of mortality, acute kidney injury (AKI), and postoperative atrial fibrillation (POAF) in ICU patients after cardiac surgery.MethodsWe conducted a retrospective cohort study utilizing data from the MIMIC-IV database. Adult patients who underwent cardiac surgery and were subsequently admitted to the ICU were included. Cox proportional hazards models were employed to assess the effect of ondansetron exposure on ICU and 28-day mortality. Multivariable logistic regression analyses examined the associations between ondansetron exposure and the incidence of AKI (2-day and 7-day) and POAF. Sensitivity analyses included Propensity Score Matching (PSM) and the inclusion of patients with ICU stays of less than 24 h to ensure robustness of results. Subgroup analyses explored the effects of age and other clinical factors, with interaction tests to examine differential impacts.ResultsA total of 7,170 were included. The incidence of AKI was 74.4% at 2 days and 76.7% at 7 days post-surgery. The 28-day postoperative mortality rate was 1.4%, while the ICU mortality rate was 1.0%. POAF occurred in 17.4% of the patients. Ondansetron exposure was not associated with 28-day mortality or ICU mortality (p > 0.05). However, after PSM, ondansetron exposure was significantly associated with an elevated risk of AKI at 2 days (OR 1.28, 95% CI 1.13–1.45, p < 0.001] and 7 days (OR 1.25, 95% CI 1.15–1.45, p < 0.001), as well as POAF (OR 1.20, 95% CI 1.04–1.39, p = 0.014).Subgroup analysis revealed a stronger association in patients aged over 65 years, where ondansetron was linked to an increased risk of 7-day AKI (OR 1.51, 95% CI 1.29–1.78, p < 0.001) and POAF (OR 1.31, 95% CI 1.12–1.53, p = 0.001). Interaction tests showed a significant interaction between ondansetron exposure and age (P for interaction = 0.018 for AKI and P for interaction = 0.02 for POAF). Sensitivity analyses, including patients with ICU stays of less than 24 h, confirmed the robustness of these findings.ConclusionIn ICU patients following cardiac surgery, postoperative use of ondansetron is associated with an increased risk of both 7-day AKI and POAF, particularly in patients aged 65 years and older. These findings suggest that the use of ondansetron in this population should be approached with caution, especially in elderly patients who may be more susceptible to these complications. Further research is needed to explore the mechanisms underlying the association between ondansetron and these adverse outcomes.